Can sustainable practices and value enhance loyalty in maritime sector? An analysis of their discriminatory capacity - Justavino-Castillo, Milva Eileen; Gil-Saura, Irene; Fuentes-Blasco, María; Moliner-Velázquez, Beatriz (Revista Venezolana de Gerencia, 2026)
This paper analyzes customer loyalty toward their main shipping service provider based on sustainable practices and logistics value. Surveys were conducted with managers in Panama’s maritime sector, collecting 140 responses evaluated using Automatic Interaction Detection (AID). The study aimed to identify which sustainability (economic, social, environmental) and logistics value (productivity, quantification, importance) dimensions influence loyalty. Three customer segments with different loyalty levels were found. Economic, social sustainability and productivity were key factors in B2B relationships. Segments also varied by business type and provider choice. Results indicate that varying perceptions of value and sustainability shape loyalty. Shipping companies should tailor services to meet client needs. Regular evaluations of customer perceptions are recommended to improve strategic alignment and loyalty.